Identifikasi Peran dan Strategi Pengembangan Kelembagaan Pertanian Paguyuban Arum Gula diKecamatan Bungbulang - Hakim, Lukmanul; Febrianti, Tintin (Ma'soem University, 2025)
The weak institutional capacity is due to the participation of members and the lack of understanding of the institutional role in the countryside. This research aims to identify the existence, role and development strategy in the institution of the Arum Gula Association. This research was carried out using a descriptive quantitative method using primary data obtained through interviews with palm farmers and secondary data obtained from related agencies such as the Agriculture Office, the Plantation Office, the Central, Statistics Agency (BPS) and previous journals. The Arum Gula Association is a farmer institution that aims to increase the independence and empowerment of palm sugar farmers. With a bottom-up leadership system, the Arum Gula Association has succeeded in strengthening the participation of its members in social, economic and environmental aspects. The role of the Association includes the provision of capital tools, market guarantees, and training that improve the social, economic, and productivity of farmers.